Pendidikan Islam pada Masa Bayi (Telaah Hadis tentang Azan bagi Bayi yang Baru Lahir) - Abu Bakar Dja'far; Fatimah Fatimah; Andi Hidayat (Islamic Review, 2021)
This research purposes to find out (1) Islamic education in infancy examines the hadith about the call to prayer for newborns (2) the status of the hadith contained in the Prophet's hadith about the call to prayer in the newborn's ear. This research is a type of library research with a qualitative approach, in which this research describes and analyzes the data in the library, namely books, magazines, news newspapers and journals, all of these materials are recorded and analyzed and then processed into research data. Primary is the main source of data directly collected by researchers from the object of research, the author examines the thoughts of Islamic education for newborns and the hadith about the call to prayer for newborns in the book Sunan Abu Dawud, Sunan al-Tirmidhi, Musnad Ahmad ibn Hambal. The status of the Hadith regarding the call to prayer for newborns is a weak hadith due to one of the weak narrators, namely Asim bin Ubaidillah. The educational values ​​contained in the call to prayer are the first monotheism education which is reflected in the sentenceAllahu Akbar, Allahu Akbar', Ashhadu allaa illaaha illallaah' Ashhadu anna Muhammadar rasuulullah' Second, ubudiyah education or worship which is reflected in the sentence Hayya 'alashshalaah, the third moral education which is reflected in the sentence Hey 'alalfalaah'.